Evaluation of interfaces presenting information to a person in terms of visual fields and the amount of information provided - Shohei TAKAOKA (The Japan Society of Mechanical Engineers, 2020)
Methods for presenting information by utilizing a visual field (such as driver peripheral vision) are attracting increased attention in association with an increase in the amount of information required for driver assistance. However, studies on interfaces utilizing such a visual field are currently insufficient. In addition, to avoid information overload, it is important to evaluate different interfaces in terms of the amount of information presented. The authors researched those interfaces from the viewpoint of ergonomics with the purpose that the result is possible to be applied to various researches mainly in the field of automobiles. Through an in-house experiment, participants viewed video clips presenting dot patterns within their peripheral vision or effective visual field (which is nearer to the gazing point than peripheral vision), and then answered questions regarding the positions and moving directions of the dots and the mental workload they experienced. The authors prepared two types of dotted patterns (fixed and moving) based on the perceptive characteristics of peripheral vision. The number of dots varied from one to six. The rate of misperception and participant mental workload were calculated. The results showed a tendency for the effect of the visual fields to depend on the type of dot pattern. It appears that the interface for peripheral vision may have resulted in a lower accuracy when fixed objects were presented, whereas fewer differences occurred when moving dots were shown. This implies that information with motion can be more suitable for interfaces utilizing peripheral vision. A larger amount of information and number of tasks resulted in lower accuracy and higher workload. Moreover, the relation between the number of dots and the rate of misperception (estimated based on percentage) suggests that the rate of misperception may increase significantly when either four or more fixed objects, or three or more moving objects, are presented.